2015
DOI: 10.5539/ies.v8n9p120
|View full text |Cite
|
Sign up to set email alerts
|

Developing Language Learning Textbooks Enriched with Sense of Literacy: The Case of Junior High School in Indonesia

Abstract: This research is aimed at developing an Indonesian course-books integrated with the materials for life skill education (LSE). It can support effective learning through literacy models and results qualified book on Indonesian language learning. By applying Fenrich's method on development model (1997) include five phases of analysis, planning, constructing, developing, and implementation, analysis was carried out by focusing on the synergy of the basic competence (BC) compared to the competency of general life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The qualified instructional books can resolve students' problems in order to achieve educational goals (Helaluddin, 2018;Hariadi et al, 2018). It can be said that instructional books include knowledge, skills, and attitudes that have to be mastered by students to fulfill the standard competences as stated by Sodiq (2015), it becomes teacher's responsibility in building creativity to create innovative instructional books.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualified instructional books can resolve students' problems in order to achieve educational goals (Helaluddin, 2018;Hariadi et al, 2018). It can be said that instructional books include knowledge, skills, and attitudes that have to be mastered by students to fulfill the standard competences as stated by Sodiq (2015), it becomes teacher's responsibility in building creativity to create innovative instructional books.…”
Section: Introductionmentioning
confidence: 99%
“…A gap in learning and mastering Indonesian language especially in writing scientific papers can be viewed in several studies such as in Darmuki (2014), Sodiq (2015), Helaluddin (2018), andHariadi, et al (2018). It is revealed that Indonesian language is a course with low credit semester.…”
Section: Introductionmentioning
confidence: 99%
“…Another thing in language textbooks that also gets attention is the development of materials, assignments, and redesigns of language textbooks that are more meaningful, which need to start with a needs analysis Owen, (2015;Wang, 2019), including the provision of language textbooks that are integrated with network facilities to make it easier for students to access them Gumono, (2021); Kessler, (2018); Lian et al, (2021). In particular, in the context of Indonesian textbooks, Sodiq (2015) conducted research on the development of Indonesian language textbooks integrated with life skills material education to support effective learning through literacy models and quality book products to ensure the achievement of higher-order thinking learning.…”
Section: Introductionmentioning
confidence: 99%
“…According to the purpose of higher education in Act No.12 of 2012 which is reflected in the learning of Bahasa Indonesia/general education, learning Bahasa Indonesia can provide information, challenges, and encouragement, enrich experiences, improve mental and social sensitivity, develop self-confidence and the ability to formulate, dig up, and process information, and improve the courage to take decisions that have become the nature of language learning [1] The main development in this fast-track study is that the students who win the "Fast Track" competition, whether in a group or individually, will automatically qualify for earning points. Bonus points for various eligible learning challenges will gain points in every meeting.…”
Section: Introductionmentioning
confidence: 99%